Improving the Competence of SMEs Customers through Mentoring: Holding BRI and PT Permadani Nasional Mandiri - Yudi Wahyudin Suwandi (AIBPM Publisher, 2024)
This study investigates competency-based MSME mentoring following the holding between Bank Rakyat Indonesia (BRI) and PT Permadani Nasional Mandiri (PNM). This study aims to evaluate the impact of competency-based mentoring on micro entrepreneurs and the growth of the MSME sector, as well as identify factors that influence the implementation of such mentoring. The research method involves secondary data analysis, interviews with expert judgment, and literature review to understand the concept of competency- based mentoring. The results show that competency-based mentoring conducted by PT PNM after holding with BRI has a positive impact on micro entrepreneurs and the growth of the MSME sector. The MSME customers who received this mentoring experienced improved performance in various aspects of their business, including financial performance, management, marketing, and competitiveness. Based on these findings, the study recommends a more targeted strategy in competency-based mentoring, including personalization of mentoring, development of a targeted competency development plan, training and skills upgrading, mentoring, and periodic evaluation.